Sol-gel derived glass films and their hybridization with InP based optoelectronics for novel optical communications devices - Liu, Jian. (2008)
This thesis summarizes the theoretical and experimental study for the project entitled “Sol-Gel Derived Glass Films and Their Hybridization with InP Based Optoelectronics for Novel Optical Communication Devices” for my PhD program. The advantages, challenges, and further applications for this project are thoroughly analyzed.